2011
DOI: 10.1063/1.3614561
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature and narrow intersubband electroluminescence from ZnCdSe/ZnCdMgSe quantum cascade laser structures

Abstract: We report ZnCdSe/ZnCdMgSe Quantum Cascade structures with “two-phonon” and “bound-to-continuum” active region designs. The electroluminescence shows more than 3 times higher luminescence efficiency and 40% narrower linewidth (<30 meV) than previous reports. The measured turn-on voltage matches closely the calculated value, indicating the improved electron transport characteristics in these structures. A waveguide design suitable for mode confinement in this material system is also presented, which resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The above mentioned dependence of the ISB gain on the m can be used to estimate the potential of other material systems that being investigated, but where QCL operation has not been demonstrated yet. While the concept of intersubband emission could be extended to a wider range of materials, this evaluation is limited to materials, where electroluminescence has been demonstrated up to date . Experimental EL data of established material systems are used to obtain a fit function with one free parameter .…”
Section: Design Considerationsmentioning
confidence: 99%
“…The above mentioned dependence of the ISB gain on the m can be used to estimate the potential of other material systems that being investigated, but where QCL operation has not been demonstrated yet. While the concept of intersubband emission could be extended to a wider range of materials, this evaluation is limited to materials, where electroluminescence has been demonstrated up to date . Experimental EL data of established material systems are used to obtain a fit function with one free parameter .…”
Section: Design Considerationsmentioning
confidence: 99%
“…Savic et al reported on design and simulation results of ZnMnSe/ ZnMgSe spin‐polarized THz QCL tunable by magnetic field, which are emitting in regions of 2.4–6.3 THz and 9.2–10.1 THz at 1.5 K. The design and simulation results of magnetically‐tunable optically‐pumped THz QCL lasers based on ZnMnSe/ZnCdMgSe with wavelengths of 60–72 μm at temperature of 77 K and magnetic fields up to 50 Tesla were reported by Popadic et al . The successful room‐temperature intersubband electroluminescence from ZnCdSe/ZnCdMgSe quantum cascade laser structures were experimentally demonstrated by Yao et al in 2011. They used quantum cascade structures with ”two‐phonon” and ”bound‐to‐continuum” designs with improved 3 times electroluminescence efficiency and 40% narrower linewidth (<30 meV).…”
Section: Introductionmentioning
confidence: 98%
“…Also, intersubband infrared devices based on this material system are the most advanced outside the well-established III–V materials. Specifically, room temperature electroluminescence from quantum cascade structures has been demonstrated at 4.7 μm [8,9] and 6.8 μm [10]. Additionally, quantum well infrared photodetectors (QWIPs) with performance comparable to those made with III–V materials [11] have been reported.…”
Section: Introductionmentioning
confidence: 99%